Web-Based Teacher Attendance Information System Using RFID Cards (Radio Frequency Identification) At SMPN 2 Sukahening Tasikmalaya: Riyan Wiranatakusumah, Missi Hikmatyar, Yusuf Sumaryana - Wiranatakusumah, Riyan; Hikmatyar, Missi; Sumaryana, Yusuf (Journal of Multidisciplinary Research, 2025)
The Web-Based Teacher Attendance Information System Using RFID (Radio Frequency Identification) Cards at SMPN 2 Sukahening Tasikmalaya aims to improve the efficiency and accuracy of teacher attendance recording. Currently, the attendance system at SMPN 2 Sukahening is still conducted manually, which is prone to errors, inefficient, and difficult to monitor in real-time. This research proposes the development of a web-based attendance system integrated with RFID technology to address these issues. The system is designed using PHP programming language, MySQL database, and hardware components such as RFID cards and RFID Reader. The system development method used is the Waterfall method, which includes stages of requirement analysis, system design, implementation, and testing. The results show that the system is capable of automatically recording teacher attendance, providing accurate attendance data, and enabling real-time monitoring through a web-based platform. This system is expected to enhance transparency, efficiency, and accuracy in managing teacher attendance at SMPN 2 Sukahening.